LEGAL PROTECTION FOR REFILLABLE GALLON CONSUMERS DUE TO BISPHENOL A (BPA) CONTENT - Ayu Citra Santyningtyas; Edi Wahjuni; Fathu Burhannudin Fajri (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
The purpose of this study is to determine how the legal protection and dispute resolution efforts of consumers who are harmed due to the presence of Bisphenol A (BPA) content in refillable gallon packaging. This research is motivated by BPOM's findings on the migration of Bisphenol A content in 6 (six) regions (Medan, Bandung, Manado, Jakarta, Banda Aceh and North Aceh) in an alarming condition and exceeds the threshold in Medan and North Aceh where the Bisphenol A threshold is 0.6 ppm. This research uses normative juridical by adjusting legal issues with applicable legal norms. The data in this research uses secondary data relevant to the research. The results of this study reveal that Bisphenol A can endanger human health such as emotional disorders in children, therefore the need for legal protection in the form of clear and honest information about Bisphenol A in the form of labels on refillable gallon packaging which aims to encourage businesses to be careful in the production process. Dispute resolution efforts for consumers who are harmed can be through the court and out of court.